2016
DOI: 10.3892/ol.2016.5245
|View full text |Cite
|
Sign up to set email alerts
|

Receptor FGFRL1 acts as a tumor suppressor in nude mice when overexpressed in HEK 293 Tet-On cells

Abstract: Fibroblast growth factor receptor-like 1 (FGFRL1) is a transmembrane receptor that interacts with heparin and FGF ligands. In contrast to the classical FGF receptors, FGFR1 to FGFR4, it does not appear to affect cell growth and proliferation. In the present study, an inducible gene expression system was utilized in combination with a xenograft tumor model to investigate the effects of FGFRL1 on cell adhesion and tumor formation. It was determined that recombinant FGFRL1 promotes the adhesion of HEK 293 Tet-On®… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…FGFRL1 is newly described and usually expressed in adult pancreas and embryonic bone ( 34 ). A study has demonstrated that FGFRL1 overexpression in HEK 293 Tet-On cells suppresses the development of tumor in nude mice ( 35 ). For another example, FGFRL1 can't enhance cell proliferation but induce cell adhesion ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…FGFRL1 is newly described and usually expressed in adult pancreas and embryonic bone ( 34 ). A study has demonstrated that FGFRL1 overexpression in HEK 293 Tet-On cells suppresses the development of tumor in nude mice ( 35 ). For another example, FGFRL1 can't enhance cell proliferation but induce cell adhesion ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…No function has been attributed to the short intracellular histidine‐rich domain of FGFRL1, as mice in which this domain is replaced with green fluorescent protein (GFP) are phenotypically normal (Bluteau et al, 2014). The critical molecular functions of FGFRL1 are not well defined; however, proposed functions include binding FGF ligands as a decoy receptor, dimerization‐induced inhibition of tyrosine kinase FGFRs, modulation of receptor turnover or signaling, or FGF‐independent regulation of cell adhesion or cell fusion (Trueb, 2011; Zhuang et al, 2016). Other studies show that FGFRL1 may activate FGF signaling pathways and promote resistance to chemotherapy in small cell lung cancer cell lines (R. Chen, Li, Zheng, et al, 2020).…”
Section: Regulation Of Fgfr Signal Transduction By Extracellular and ...mentioning
confidence: 99%
“…The biological function of FGFR5 is unclear. A recent study suggested that it functions as a cell-cell adhesion protein, acting as a tumor suppressor gene [10].…”
Section: The Fgfr/fgf Systemmentioning
confidence: 99%